Mineralogy, Geochemistry, and Laboratory Spectroscopic Study of Plasma Generated around Meteorites using an Nd: YAG Laser - Ahmed, Abdullah K.; Yaseen, Waleed Ibrahim; Al-Jubury, Harth E. (Iraqi Journal of Science, 2026)
Meteorites are a crucial subject that assists in comprehending the components of the solar system. They burn entirely or partially when they enter the atmosphere due to friction. A plasma will generate surroundings and finally a mass ablation. By studying the spectrum of the forming plasma around them, we can investigate the chemical compositions of the meteorites’ mass and the parameters of the plasma. In this work, a laboratory study was conducted on a genuine meteorite that fell in the city of Baghdad. A sample was taken from the meteorite and bombarded with a laser to obtain plasma. Optical emission spectroscopy was used to diagnose plasma parameters using the Boltzmann method and LIBS (Q-switched Nd: YAG pulsed laser). A vacuum chamber was used to experiment under a working pressure of 0.1 mbar. Additionally, laser energies ranged from 600 mJ to 1000 mJ, and a Thorlabs spectrometer with an operating range of 320 nm to 740 nm were used. Plasma parameters were calculated using atomic iron Fe I various peaks. The electron temperature, density, length of Debye, and plasma frequency rose in the meteorite surrounding plasma as a response to the laser energy increase. For the mineralogical composition, meteorite samples have a simple silicate composition. The minerals found were diopside pyroxene (augite), serpentine talc, and secondary magnetite. The main composition is lazurite, which is mainly composed of fine-crystalline grains that directly replace the olivine grains.